The frequency of toll-like receptor 4 gene polymorphism in ankylosing spondylitis and its relationship between disease activity - Sargın, Betül; Akbal, Ayla; Resorlu, Hatice; Savaş, Yılmaz; Zateri, Coşkun; Sılan, Fatma; Özdemir, Öztürk (The European Research Journal, 2018)
Objectives. We aimed to evaluate the frequency of toll-like receptor 4 (TLR4) gene polymorphism and its relationship between disease activity in patients with ankylosing spondylitis (AS). Methods. Forty-one AS patients (25 male/16 female) fullfilling the 1984 Modified New York Criteria and 41 healthy controls (25 male/16 female) were included in this study. Disease activity of the AS patients was assesed by Bath Ankylosing Spondylitis Disease Activity Index (BASDAI). The TLR4 gene polymorphism of AS patients and healthy controls were analyzed by Real-Time Polymerase Chain Reaction (PCR) System. Results. Three (7.3%) patients with AS had TLR4 gene polymorphism compared with healthy controls (0/41; 0%). Two of these patients had heterozygous mutation and one had homozygous mutation. Significant correlation was not found between TLR4 gene polymorphism and BASDAI score (p > 0.05). Conclusions. In our study, TLR4 gene polymorphism was higher in patients with AS compared with control group. But, this polymorphism was not associated with disease activity, erythrocyte sedimentation rate and C-reactive protein levels.﻿